Changes in Long‐Term Glucocorticoid Use Among Older Adults After New Diagnosis of Late‐Onset Rheumatoid Arthritis - Jiha Lee; Jonathan Martindale; Beth I. Wallace; Namrata Singh; Una E. Makris; Julie P.W. Bynum (ACR Open Rheumatology)
Background We evaluated changes in long‐term glucocorticoid (GC) use and factors associated with persistent GC use in older adults with late‐onset rheumatoid arthritis (LORA). Methods Using 20% Medicare data from 2008 to 2017, we identified adults ≥66 years with a new diagnosis of LORA, disease‐modifying antirheumatic drug (DMARD) use or at least two rheumatologist visits, and at least 12 months of follow‐up data. Older adults were categorized as DMARD‐exposed or DMARD‐unexposed based on treatment during the 12 months after LORA diagnosis (index date). For each quarter after the index date, long‐term GC use was defined as having oral GC prescriptions for at least 30 days with a dose >5 mg/day prednisone equivalent. We compared long‐term GC use between quarter (Q)1 and Q4 and performed stratified mixed‐effects logistic regression for factors associated with persistent GC use, defined as long‐term GC use in Q2 to Q4. Results The cohort included 15,425 individuals with two‐thirds (62.5%) being DMARD‐exposed. Between Q1 and Q4, the proportion of older adults on long‐term GC declined from 44.1 to 24.9% (∆19.2%) among the DMARD‐exposed and from 25.8 to 17.9% (∆7.9%) among the DMARD‐unexposed. One year after the index date, 13.5% of the DMARD‐exposed and 9.8% of the DMARD‐unexposed were persistent GC users. In stratified mixed‐effects logistic models, persistent GC use was associated with low‐income subsidy status among the DMARD‐exposed and with greater comorbidity burden among DMARD‐unexposed. Conclusion Long‐term GC use declined more among DMARD‐exposed than DMARD‐unexposed patients. One in seven DMARD‐exposed and one in ten DMARD‐unexposed have persistent GC use which is associated with financial barriers and multimorbidity that may limit the use of steroid‐sparing DMARDs.